Eficácia do consumo de arroz fortificado com ferro no tratamento de crianças com anemia carencial - Milene Cristine Pessoa (2009)
Anemia is one of the most serious micronutrient deficiency problems, and can be found throughout the modern world as a public health matter. Food fortification has been used as aneffective strategy to reduce iron deficiency among peoples of many nations. This study aimsto assess the efficacy of an experimental intervention in the control of iron deficiency anemiaamong children by introducing fortified rice in therapeutic doses. It was developed from October 2007 to February 2008 in two municipalities of the Belo Horizonte metropolitan region (Brazil). Children of between 6 to 24 months of age, who were diagnosed with serumhemoglobin in the 8.0 to 11.0 g/dl range, were randomly distributed into two groups: the UltraRice (UR) group, which received ferric pyrophosphate fortified rice, and the Drug Supplement (DS) group, which received ferrous sulfate three times a week (0.8mg/Kg; 3d/wk). In other words, the UR group received a placebo, while the DS group received conventional rice. Hemoglobin levels, serum ferritin (SF), and C-reactive protein (CRP) weremeasured before and five months after intervention. From 194 eligible children, only 174 completed the trial. After five months of intervention, mean values of Hemoglobin were 10.6± 1.0 g/dl (UR) and 10.7 ± 0.8 g/dl (DS) (p<0.05), whereas mean values of SF were 13.9 ± 5.4 g/l (UR) (p<0.05) and 12.1 ± 7.0 g/l (DS) (p<0.05). The UR group presented a higher rise in hemoglobin concentrations and SF mean levels (p<0.01). By the end of study, anemiaprevalence had been reduced in both the UR (34.9%) and the DS (14.3%) groups (p<0.01). Inthe UR group, multivariate analysis demonstrated a lesser risk of remaining anemic (RR=0.73; CI95% 0.61 - 0.88) among children with normal stature for age (RR=0.79; CI95%0.67 - 0.93), with an increase in SF levels (RR=0.98; CI 95% 0.96 0.99), and with an increase in age (RR=0.97; CI95% 0.96 0.99). Results show that iron fortified foods are aneffective strategy to preventing and controlling iron deficiency anemia. These findings also reveal their potential to be incorporated in programs that can stimulate their consumption inat-risk populations.